Biomass production, nutrient uptake and partitioning in planted Senna spectabilis, Flemingia macrophylla and Dactyladenia barteria fallow systems over three fallow/cropping cycles on Ultisol - Hauser, S. (Informa UK Limited, 2008)
Biomass production and nutrient uptake of all components in planted Senna spectabilis, Dactyladenia barteri and Flemingia macrophylla hedgerow fallow were determined after three two-year fallow phases and compared to natural fallow. Total above-ground biomass production after each of three fallow phases was significantly higher in the Senna system than any other system. Total above ground biomass production in the Flemingia and the Dactyladeniai system was not different from that in natural fallow. The volunteer biomass between hedgerows was only once significantly reduced by S. spectabilis during the first fallow phase. The amount of litter did not differ between fallow systems. The biomass of S. spectabilis, F. macrophylla and D. barteri comprised 96%, 95% and 65% wood, respectively. Relative to the total system biomass, wood constituted 67% in S. spectabilis and about 20% in F. macrophylla and D. barteri systems. Except for Mg, the S. spectabilis system accumulated more nutrients in above ground biomass than any other system. The highest nutrient uptake achieved in the S. spectabilis system was 335 kg ha71 N, 331 kg ha71 Ca, 230 kg ha71 K, and 39 kg ha71 P. Relative to the S. spectabilis system, nutrient accumulation, except for Mg, was the lowest in the natural fallow control followed by the F. macrophylla and the D. barteri system. In F. macrophylla and S. spectabilis, 95% and 85% of the nutrients were accumulated in the wood. In D. barteri the nutrient distribution between leaves and wood was approximately equal. Export of wood would remove 9–16% of the nutrients accumulated in the F. macrophylla and D. barteri systems but 27–53% in the S. spectabilis system. Potential consequences of different biomass management options for crop yields and fallow re-growth are discussed.